Effect of Clopidogrel on Thrombus Formation in an Ex Vivo Parallel Plate Flow Chamber Model Cannot Be Reversed by Addition of Platelet Concentrates or vWF Concentrate. (April 2017) - Jahn, Kira; Suchodolski, Klaudiusz; Schäfer, Andreas; Sahlmann, Bianca; Küster, Uwe; Echtermeyer, Frank; Calmer, Simone; Theilmeier, Gregor; Johanning, Kai
Abstract : BACKGROUND: Hemorrhage is the most important complication of antithrombotic therapy with P2Y12 receptor blockers. The administration of platelet concentrates (PCs) and von Willebrand factor (vWF) concentrates are common procedures to normalize impaired primary hemostasis in bleeding patients. We tested whether this strategy reverses the effect of clopidogrel using a parallel plate flow chamber model. METHODS: Whole blood from patients, who received a loading dose of clopidogrel with 600 mg and an ongoing dual antiplatelet therapy with 75 mg/d clopidogrel and 100 mg/d acetyl salicylic acid, compared with blood from healthy volunteers was examined in a collagen-coated parallel plate flow chamber. Blood was perfused by suction at a shear rate of 300/s, which is equivalent to 14 dynes/cm 2 to resemble shear stress in conduit arteries. Platelet-covered area, individual thrombus size, and the average thrombus size were assessed morphometrically. The equivalent of 2 or 5 units of PC and/or 2 U/mL of vWF concentrate were used in an attempt to restore coagulation capacity in blood samples of clopidogrel-treated patients. RESULTS: In this model, clopidogrel reduced the increase of thrombus size. The equivalent of 2 U of PC or 2 U/mL of vWF alone did not show any significant changes in thrombus size. 5 U of PC increased thrombus size in clopidogrel-treated patients ( P < .05). Thrombus size in clopidogrel blood was increased by combined PC and vWF treatment (by 50%, P < .05), but this increase did not reach control levels ( P < .05). CONCLUSIONS: This flow chamber model is suitable for detection of the antiplatelet effect of clopidogrel. Ex vivo addition of PC or vWF does not overcome the effects of clopidogrel in this model, but the combination of both shows a mild and significant improvement in thrombus size.